Expanding Possibilities for Foreign Gene Expression by Cucumber Green Mottle Mosaic Virus Genome-Based Bipartite Vector System - Chattopadhyay, Anirudha; Jailani, A. Abdul Kader; Roy, Anirban; Mukherjee, Sunil Kumar; Mandal, Bikash (Plants (Basel), 2024)
Expanding possibilities for foreign gene expression in cucurbits, we present a novel approach utilising a bipartite vector system based on the cucumber green mottle mosaic virus (CGMMV) genome. Traditional full-length CGMMV vectors face limitations such as a restricted cargo capacity and unstable foreign gene expression. To address these challenges, we developed two ‘deconstructed’ CGMMV genomes, DG-1 and DG-2. DG-1 features a major internal deletion, resulting in the loss of crucial replicase enzyme domains, rendering it incapable of self-replication. However, a staggered infiltration of DG-1 in CGMMV-infected plants enabled successful replication and movement, facilitating gene-silencing experiments. Conversely, DG-2 was engineered to enhance replication rates and provide multiple cloning sites. Although it exhibited higher replication rates, DG-2 remained localised within infiltrated tissue, displaying trans-replication and restricted movement. Notably, DG-2 demonstrated utility in expressing GFP, with a peak expression observed between 6 and 10 days post-infiltration. Overall, our bipartite system represents a significant advancement in functional genomics, offering a robust tool for foreign gene expression in Nicotiana benthamiana.